(untitled) (Journal of Entrepreneurship and Business, 2021)
Globally, the need for entrepreneurial activities for young graduates has become an important area of concern for researchers and policy makers. However, one of the main concerns that warrants this research to be undertaken is the low number of graduates going into entrepreneurship. Therefore, we aim to address this concern by investigating the effects of entrepreneurial education on entrepreneurial intentions, while appreciating the role of perceived social support as a moderating variable. We strive to achieve the objective of this work by employing cross sectional research design. Our data were collected through the use of self-completed questionnaire that was distributed to 398 undergraduate students of the largest University in sub-Saharan Africa. The data collected were further analysed using SmartPLS software for Partial Least Squares modelling. The findings showed that entrepreneurship education has insignificant positive effect on entrepreneurial intention. Most importantly, the findings show that the interaction between Perception of Social Support and Entrepreneurship Education on Entrepreneurial Intention was significant. The result demonstrated in this work provides important implications for policy makers responsible for entrepreneurship development. In particular, an understanding of the factors that could lead to the formation of entrepreneurial intentions prove to be important for managers responsible for promoting and facilitating entrepreneurship programmes.